2003
DOI: 10.1177/120347540300700601
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Invasive Cutaneous Melanoma in Saskatchewan 1970–1999

Abstract: The observed increase in melanoma appears to be real and not the result of increased surveillance or screening. Tumor characteristic (Breslow depth, Clark level) and gender were significant prognostic indicators of five-year excess mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 61 publications
3
16
1
2
Order By: Relevance
“…9 An approximate 3-fold increase in the incidence rates was noted for both men and women between these two decades, which correlates with similar increases observed in other Canadian provinces. 7 However, during the course of the present period of study from 1993 to 2002, we observed a plateau in incidence and the suggestion of decreasing incidence rates in recent years from 1999 to 2002 (see Fig 3).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…9 An approximate 3-fold increase in the incidence rates was noted for both men and women between these two decades, which correlates with similar increases observed in other Canadian provinces. 7 However, during the course of the present period of study from 1993 to 2002, we observed a plateau in incidence and the suggestion of decreasing incidence rates in recent years from 1999 to 2002 (see Fig 3).…”
Section: Discussionmentioning
confidence: 69%
“…7,13 When countrywide Canadian incidence rates were plotted for the 12-year period 1993-2004, 5 a plateau effect was noted for both men and women (see Fig 4). This information places a new perspective on Canadian melanoma incidence rates that were previously reported to be similar to other increasing melanoma rates worldwide.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Malignant melanoma is one of the fastest growing cancers worldwide; studies from Europe (de Vries and Coebergh, 2004; Lasithiotakis et al , 2006; Mansson-Brahme et al , 2002; Stang et al , 2006), Singapore (Koh et al , 2003) Canada (Ulmer et al , 2003) and the United States (Dennis, 1999; Geller et al , 2002; Hall et al , 1999) suggest consistent and dramatic increases in incidence since the 1950s. Yet the underlying causes of these observed trends are widely debated (Florez and Cruces, 2004; Lamberg, 2002; Swerlick and Chen, 1996, 1997), with some authors attributing the rapid rises to environmental risk factors and sun exposure behavior (Diffey, 2004), and others maintaining they result from expanded screening, biopsy (Welch et al , 2005), and reporting of lower-risk melanomas to cancer registries (Hall et al , 2003; Swerlick and Chen, 1996, 1997), notions supported by relatively stable trends in melanoma mortality for most groups.…”
Section: Introductionmentioning
confidence: 99%
“…In Canada, an estimated 6800 new cases of cutaneous melanoma and 1150 related deaths were predicted for 2015 13 . In addition, evidence suggests that the incidence of cmm across Canada is increasing, a trend that has also been seen in other countries worldwide [13][14][15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%